PENGARUH JUS TOMAT TERHADAP PROFIL LIPID PADA PENDERITA DISLIPIDEMIA - Sugini (UNIVERSITAS NGUDI WALUYO, 2019)
Background :High LDL cholesterol can develop into atherosclerosis. Tomatoes contain lots of lycopene which plays a role in protecting fat from peroxidation which reacts with hydroperoxyl fat by binding to free radicals. Lycopene is known to play a role in preventing several important chronic diseases, one of which is atherosclerosis. Method :The research design was a quasi experiment control design with pre post test. The subjects of the study were 62 employees of Kendal Hospital, aged 35-50 years, suffering from dyslipidemia and not suffering from metabolic or degenerative diseases based on the examination of a specialist in internal medicine. Subjects were divided into 2 groups, each with 31 subjects. Group I was given ripe tomato juice 336 grams per day for 21 days and group II as a control. Data analysis using Kolmogorov Smirnov test, Mann Whitney test and Independent Samples t-test.Conclusion withdrawal uses a confidence level of 95% (α = 0.05). Results:There was a reduction in total cholesterol levels of 29.6 gr / dl (p = 0.00), LDL levels 32.5 gr / dl (p = 0.00), triglyceridelevels 41.4 gr / dl (p = 0.01). Conclusion :The administration of tomato juice can reduce total cholesterol, LDL and triglyceride Abstrak : Latar Belakang : Kadar kolesterol LDL yang tinggi dapat berkembang menjadi aterosklerosis. Tomat mengandung banyak likopen yang berperan dalam melindungi lemak dari peroksidasi yang bereaksi dengan hidroperoksil lemak dengan cara mengikat radikal bebas. Likopen diketahui mampu berperan mencegah beberapa penyakit kronis penting salah satu diantaranya aterosklerosis. Penelitian ini untuk mengetahui perbedaan perubahan profil lipid penderita dislipidemia. Metode : Rancangan penelitian adalah quasi experiment control design with pre post test. Subyek penelitian 62 karyawati RSUD Kendal, umur 35 – 50 tahun, menderita dislipidemia dan tidak menderita penyakit metabolik atau degeneratif berdasarkan dari pemeriksaan dokter spesialis penyakit dalam. Subyek dibagi 2 kelompok masing-masing 31 subyek. Kelompok I diberikan jus tomat matang 336 gram per hari selama 21 hari dan kelompok II sebagai kontrol. Analisa data menggunakan uji Kolmogorov Smirnov, uji Mann Whitney dan Independent Samples t-test. Penarikan simpulan menggunakan tingkat kepercayaan 95% (α = 0,05). Hasil Penelitian : Ada penurunan kadar kolesterol total 29.6 gr/dl (p = 0,001), kadar LDL 32.5 gr/dl (p = 0,001) , kadar trigliserida 41.4 gr/dl (p = 0,01) Simpulan : Pemberian jus tomat dapat menurunkan kadar kolesterol, kadar LDL dan kadartrigliserida